2004
DOI: 10.1007/s00198-003-1491-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and its relationship with bone mineral density in healthy Asian Indians

Abstract: Synthesis of vitamin D takes place in the skin under the effect of sunlight. The Indian subcontinent is situated between 8.4 degrees N and 37.6 degrees N latitudes and has adequate sunshine throughout the year. Thus, it has been presumed that Indians are vitamin D sufficient. We measured serum 25-hydroxy vitamin D [25(OH)D] ( n=92) and 1,25-dihydroxy vitamin D [1, 25(OH)(2)D] ( n=65) levels in healthy hospital staff, using (125)I radioimmunoassay. Serum intact parathyroid hormone (PTH) concentration was estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
151
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(175 citation statements)
references
References 26 publications
19
151
3
2
Order By: Relevance
“…7,14,15 We observed an inverse relationship of serum 25-OH-D with BMI in this study that has been previously accounted by the solubility and storage of the compound in enlarged fat mass. 16 Interestingly, Asian Indians have been included in the category of 'metabolically obese normal weight' group, as they tend to have more disproportionately higher total body fat at any given BMI compared with those of the other ethnicities 7,17 that might also lead to a false characterization of individuals as vitamin D deficient, based on their serum estimates.…”
Section: Discussionsupporting
confidence: 66%
“…7,14,15 We observed an inverse relationship of serum 25-OH-D with BMI in this study that has been previously accounted by the solubility and storage of the compound in enlarged fat mass. 16 Interestingly, Asian Indians have been included in the category of 'metabolically obese normal weight' group, as they tend to have more disproportionately higher total body fat at any given BMI compared with those of the other ethnicities 7,17 that might also lead to a false characterization of individuals as vitamin D deficient, based on their serum estimates.…”
Section: Discussionsupporting
confidence: 66%
“…It is also highly prevalent across all age groups ranging from newborns to postmenopausal women. In three different studies from North India, 96% of neonates,23 91% of healthy school girls,24 and 78% of healthy hospital staff were found to have hypovitaminosis D 25…”
Section: Discussionmentioning
confidence: 99%
“…Earlier countrywide studies have reported vitamin D deficiency as being very prevalent in India [1] even healthy young soldiers and sports woman with sufficient intake of calcium, adequate sun exposure and regular exercise regimen were found to be vitamin D deficient [7,17]. Studies have shown that the 25(OH) D levels are directly proportional to the duration of exposure to sunlight [7,18]. The amount of UV light at a geographical location depends on the length the sun's rays which have to travel through the atmosphere, where it is more or less absorbed.…”
Section: Discussionmentioning
confidence: 99%